Designing Fatigue Warning Systems: The perspective of professional drivers. (March 2016) - Meng, Fanxing; Li, Shuling; Cao, Lingzhi; Peng, Qijia; Li, Musen; Wang, Chunhui; Zhang, Wei
Abstract: Professional drivers have been characterized as experiencing heavy fatigue resulting from long driving time in their daily work. This study aimed to explore the potential demand of Fatigue Warning Systems (FWSs) among professional drivers as a means of reducing the danger of fatigue driving and to examine their opinions regarding the design of FWSs. Six focus groups with 35 participants and a questionnaire survey with 600 respondents were conducted among Chinese truck and taxi drivers to collect qualitative and quantitative data concerning the current situation of fatigue driving and opinions regarding the design of FWSs. The results revealed that both truck and taxi drivers had a positive attitude toward FWSs, and they hoped this system could not only monitor and warn them regarding their fatigue but also somewhat relieve their fatigue before they could stop and rest. As for warning signals, participants preferred auditory warnings, as opposed to visual, vibrotactile or electric stimuli. Interestingly, it was proposed that verbal warnings involving the information regarding consequences of fatigue driving or the wishes of drivers' family members would be more effective. Additionally, different warning patterns, including graded, single and continuous warnings, were discussed in the focus group. Finally, the participants proposed many other suggestions, as well as their concerns regarding FWSs, which will provide valuable information for companies who wish to develop FWSs for professional drivers. Highlights: Both truck and taxi drivers are experiencing heavy driving fatigue, and they have a positive attitude toward Fatigue Warning Systems (FWSs). Professional drivers hope FWSs could not only monitor and warn their fatigue but also somewhat relieve their fatigue before they could stop and rest. Participants prefer auditory warnings, as opposed to visual, vibrotactile or electric stimuli. Specifically, truck drivers prefer alarm warnings, while taxi drivers prefer verbal warnings. Warning patterns, concerns regarding FWSs are also discussed. The results would provide valuable information for companies who wish to develop FWSs for professional drivers.